Depth filtration application of nanofibrillated cellulose-mesoporous silica nanoparticle composites as double-layer membranes. Issue 1 (February 2022) - Miri, Simin; Nadeem, Humayun; Hora, Yvonne; Chin, Benjamin Wey Xien; Andrews, Philip C.; Batchelor, Warren
Abstract: The adsorption capacity of cellulose membranes without modification is negligible for water treatment. Therefore, enhancing cellulose adsorption capacity via cost-effective approaches is required. Double-layer membranes with a nanofibrillated cellulose (NFC) membrane and an in-situ produced NFC-mesoporous silica nanoparticles (MSN) depth filter layers were produced. The membranes were tailored to improve size rejection and saturated adsorption capacity (SAC) by altering the gram per meter square (gsm) of the depth filter layer. The higher SAC of double-layer membranes was achieved by increasing the depth filter layer gsm and because of the significantly lower porosity of double-layer membranes compared to NFC-MSN single-layer membranes. The optimized membrane for methylene blue (MB) showed the SAC of 107 mg per g of MSN. The membrane could be modified with polyethyleneimine (PEI) or polyamide amine-epichlorohydrin (PAE) resin as cationic charged polyelectrolytes for the selective adsorption of anionic molecules of metanil yellow (MY). The membrane modified with PEI had 41 times higher SAC than unmodified specimens toward MY. Optimized double-layer membranes for size rejection, including 30 gsm composite layer, were produced by reducing the NFC fibre diameter via higher homogenization and drying the NFC layer before adding the depth filter layer. The optimized double-layer membrane had a polyethylene glycol (PEG) molecular weight cut-off (MWCO) of 200 kDa. These membranes manufactured by cost-effective materials have great potential of scale-up for membrane manufacturing for water treatment. The combination of good adsorption and size rejection makes a unique material that should be explored further. Graphical Abstract: ga1 Highlights: The optimized membrane displayed high adsorption capacity and size rejection. SAC and flux of the optimized sample for MB are 107 mg per g of MSN and 7 LMH/bar. The molecular weight cut-off of the optimized membrane was 200 kDa. A tiny amount of PEI increased the adsorption of negatively charged molecules. Drying the NFC layer before adding the second layer improved the size rejection.